Peter Heather, Odrodzenie Rzymu. Cesarze i papieże: bój o władzę nad chrześcijaństwem, tłum. Janusz Szczepański, Poznań 2014, Dom Wydawniczy REBIS, ss. 515. - Kalinowski, Damian (Vox Patrum, 2014)
nie dotyczy